2016
DOI: 10.1002/pola.28439
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and mechanism of metallocene‐catalyzed olefin polymerization: Comparison of ethylene, propylene homopolymerizations, and their copolymerization

Abstract: A series of ethylene, propylene homopolymerizations, and ethylene/propylene copolymerization catalyzed with rac‐Et(Ind)2ZrCl2/modified methylaluminoxane (MMAO) were conducted under the same conditions for different duration ranging from 2.5 to 30 min, and quenched with 2‐thiophenecarbonyl chloride to label a 2‐thiophenecarbonyl on each propagation chain end. The change of active center ratio ([C*]/[Zr]) with polymerization time in each polymerization system was determined. Changes of polymerization rate, molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 79 publications
(101 reference statements)
1
24
0
Order By: Relevance
“…Similar discrepancies were identified for other metallocene based systems (e.g. 5a [58,92]). On the other hand, with the 5b/B(C6F5)3 system, very similar [C * ] values were obtained for polymerization of 1-hexene with different techniques [46,59,81].…”
Section: Critical Analysis Of Methods Implemented and Application Stusupporting
confidence: 82%
See 1 more Smart Citation
“…Similar discrepancies were identified for other metallocene based systems (e.g. 5a [58,92]). On the other hand, with the 5b/B(C6F5)3 system, very similar [C * ] values were obtained for polymerization of 1-hexene with different techniques [46,59,81].…”
Section: Critical Analysis Of Methods Implemented and Application Stusupporting
confidence: 82%
“…an aromatic chromophore group [49]) in the close proximity to the active center may be detrimental to its regular performance, thus negatively influencing the kinetics of propagation. For the quench-labelling methods, the limited or sometimes poor selectivity of the reactions between the propagating metal-polymeryl species and the labeling reagent (CO [38,65,[76][77][78][79], O2 [85], Br2 [87], TCC [91,92] As evidenced from the investigations summarized in Part 4 of this review, a comprehensive critical analysis of the results presented here is largely hampered by the different conditions used. Also, as it is often difficult to apply strictly the same conditions with one technique of active sites count to another one, direct comparison of the same catalytic systems studied by different methods cannot be straightforwardly undertaken.…”
Section: Critical Analysis Of Methods Implemented and Application Stumentioning
confidence: 99%
“…It is obvious that the kinetic studies based on direct counting of the [C*]/[Z] concentration in the polymer reaction system can permit the easier construction of a comprehensive mechanistic model. Many such studies have been reported based on different procedures of counting the active center concentration in homogenous metallocene catalyzed polymerization [ 26 , 27 , 28 , 29 , 30 ]. However, conflicting results of active centers values have been found in the literature while dealing with the same type of metallocene catalyzed polymerization, maybe because of different sensitivity levels of the methods that have been used [ 26 , 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6] Ethylene-propylene copolymer with random comonomer sequence distribution has been synthesized by homogeneous vanadium catalysts or metallocene catalysts. [7][8][9][10][11][12][13][14][15][16][17] These copolymer and EPDM with ethylene content falling in the range of 50-60 mol % are produced in large scale and applied as synthetic rubbers for their low crystallinity and excellent elastomer properties. On the other hand, ethylene-propylene copolymerization with heterogeneous Ziegler-Natta catalysts like TiCl 4 /ID/ MgCl 2 type catalysts (ID 5 ester or ether) produces copolymer with very broad composition distribution.…”
Section: Introductionmentioning
confidence: 99%
“…Ethylene–propylene copolymer with random comonomer sequence distribution has been synthesized by homogeneous vanadium catalysts or metallocene catalysts . These copolymer and EPDM with ethylene content falling in the range of 50–60 mol % are produced in large scale and applied as synthetic rubbers for their low crystallinity and excellent elastomer properties.…”
Section: Introductionmentioning
confidence: 99%